Miocene to Recent Radiolarians from Southern Pacific Coast of Costa Rica - Sandoval, María I. (2018)
Radiolarians from Miocene–Recent marine sediments are taxonomically reported for the first time in Costa Rica using samples from Sites U1381C and U1414A of the Integrated Ocean Drilling Program CRISP A2 expedition. Both sites are presently located offshore Osa Peninsula, northeastern equatorial Pacific. The sediments retrieved from the two sites mainly consist of nannofossil calcareous ooze with foraminifera, sponge spicules, diatoms and radiolarians. In both sequences, radiolarians vary from absent to abundant and well preserved. This work presents the systematic paleontology of the radiolarians recorded including taxonomic notes and illustrations of the species. An associated publication provides the statistic and biostratigraphic data for the sites, spanning from the middle Miocene to the Recent (radiolarian zones RN5 to RN16). In total, 116 species (14 families and 41 genera) were found. Hole U1414A yielded a total of 105 species and 65 taxa with conditional identifications (“species groups”), and Hole U1381C yielded a total of 90 species and 55 species groups.